COMPARISON OF ELECTRICAL ACTIVITY OF PATELLA STABILIZER MUSCLES BETWEEN ATHLETESWITH AND WITHOUT PATELLOFEMORAL PAIN SYNDROME - Yazdi, Nahid Khoshraftar; Mehdikhani, Majid; Starischka, Stephan; Zimmermann, Elke (European Scientific Journal, ESJ, 2013)
The aim of this study was to compare the electrical activity of the Tensor fascia lata (TFL) and Vastus lateralis (VL) muscles as lateral stabilizers and the Vastus medialis oblique (VMO) muscle as medial stabilizer of the patella in athletes with and without patellofemoral pain syndrome (PFPS). Eleven healthy athletes (4 women, 7 men) and 9 athletes with PFPS (3 women, 6 men) ranging in age from 20 to 30 years performed the submaximal isometric knee extension contraction initiated from 45°of flexion and an extended position to 30° and 15°angles. The activation amplitude of the TFL, VL and VMO muscles were quantified from the recorded electromyographic (EMG) signals. The results showed that Electrical activity of the VMO muscle at 30° and 45° angles for the patients was significantly greater than those of the control subjects. No significant differences were demonstrated in VMO: VL and VMO: TFL across all knee flexion angles between groups. However, the mean value of the ratio of VMO: (TFL + VL) at an angle of 30° for the subjects with PFPS was significantly greater than that of the control group. It may be assumed that the higher electrical activity of the VMO at 30° angle in PFPS patients is an effort to prevent more lateral patella tracking. Since the TFL and VL muscles produce lateral force on the patella, both of them should be studied for consideration of lateral stabilizers of the patella in the patients with PFPS.